(untitled) (Jurnal Matematika, Statistika dan Komputasi, 2025)
Let G=(V,E) be a connected graph, where V is the set of vertices and E is the set of edges of G. The kite graph, denoted by Kiten,m, is a graph obtained by appending a complete graph Kn to a pendant vertex of path Pm. This research investigates the spectrum of antiadjacency matrix of kite graph. The antiadjacency matrix of a graph G of order n is a square matrix with order n where the entries of the matrix represent the nonadjacency of the vertices.